He Saw Me and Smiled (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2023)
This piece is my take on the College Scholars application prompt in which we had to write a two-page paper featuring a grape, giraffe, and guitar. I saw them as metaphors for a fragile mind state—the confrontation of which was the only way to grow. Blending the abstract with reality, “He Saw Me and Smiled” illustrates that as daunting as it is, taking the first step—however small—means the potential for something great.For additional context, watch the author's reflection on the piece below.